2009
DOI: 10.2353/ajpath.2009.080523
|View full text |Cite
|
Sign up to set email alerts
|

HMGA2 Maintains Oncogenic RAS-Induced Epithelial-Mesenchymal Transition in Human Pancreatic Cancer Cells

Abstract: Pancreatic cancer is a highly aggressive malignancy due to elevated mitotic activities and epithelial-mesenchymal transition (EMT). Oncogenic RAS and transforming growth factor-␤ signaling are implicated in these malignant features. The mechanisms that underlie EMT need to be addressed since it promotes tissue invasion and metastasis. The high-mobility group A protein 2 (HMGA2) is a non-histone chromatin factor that is primarily expressed in undifferentiated tissues and tumors of mesenchymal origin. However, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
155
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(169 citation statements)
references
References 46 publications
10
155
0
Order By: Relevance
“…In this regard, ras mutations seem to be low in American males, whereas 25% of Japanese patients have the mutated ras gene and show a correlation with tumor stage and grade, suggesting ethnic differences exist in frequency of ras mutation in prostate cancer (42,43). However, in contrast to these findings, immunohistochemical studies revealed a strong epithelial staining for ras in the vast majority of prostate cancers.…”
Section: Role Of Ras In Prostate Cancermentioning
confidence: 88%
See 1 more Smart Citation
“…In this regard, ras mutations seem to be low in American males, whereas 25% of Japanese patients have the mutated ras gene and show a correlation with tumor stage and grade, suggesting ethnic differences exist in frequency of ras mutation in prostate cancer (42,43). However, in contrast to these findings, immunohistochemical studies revealed a strong epithelial staining for ras in the vast majority of prostate cancers.…”
Section: Role Of Ras In Prostate Cancermentioning
confidence: 88%
“…Interestingly, Watanabe et al (45) found that oncogenic ras signaling can induce HMGA2 expression (i.e., highmobility group protein A2), a gene induced during epithelial mesenchymal transitions (46), and promote malignancy of pancreatic cancer cells. In this connection, 3 groups (47)(48)(49) showed that HMGA2 translation is blocked by let-7a in cancer cells.…”
Section: Role Of Ras In Prostate Cancermentioning
confidence: 99%
“…In the study of 60 cancer cell lines, Peter's research group found that HMGA2 is one of a few gene markers that can distinguish most type I (express mesenchymal gene signature) from 0 C1 C2 C3 C4 C5 C6 C7 C8 C9 C10 C12 C13 C15 C16 C17 C19 C20 C21 C23 C24 C25 C26 C27 C28 C29 C30 C1 C2 C3 C4 C5 C6 C7 C8 C9 C10 C11 C12 C15 C13 C14 C16 C17 C18 C19 C20 0V-PSC FT EMC type II (express epithelial gene signature) cancer cell lines. 9,16 HMGA2 participates in epithelialmesenchymal transition, 25,26 a key step in tumor plasticity by converting adherent epithelial cells to motile mesenchymal cells 27 through the functional loss of E-cadherin, which is required to maintain epithelial cell-cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…25,30 The function of HMGA2 in behaviors of aggressive tumor growth in ovarian high-grade papillary serous carcinomas deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Several important oncogenes have been identified as the targets of let-7, including RAS, MYC and HMGA2 (Johnson et al, 2005;Mayr et al, 2007;Chang et al, 2008). These target genes, making use of the RAS-MEK pathway contribute to EMT, though let-7 miRNA-mediated HMGA2 downregulation had no effect on the prevention of the transformed phenotype in pancreatic cancer cells (Watanabe et al, 2009). Another let-7 miRNA-mediated tumor metastasis-regulating pathway was addressed recently: Raf kinase inhibitory protein, which inhibits mitogenactivated protein kinase signaling cascades, can decrease transcription of LIN28 by Myc.…”
Section: Microrna and Metastasis H Zhang Et Almentioning
confidence: 99%